PERAN NELAYAN PEREMPUAN DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA DI SINDANGLAUT, KAWASAN WISATA PANTAI CARITA, PANDEGLANG - Amalya, Neneng Tita; Sulistyani, Tri; Harsono, Yhonanda (SEPAKAT Sesi Pengabdian pada Masyarakat, 2023)
The purpose of this community service activity (PKM) is to spread enthusiasm in running a business that although at a small level, the benefits for family welfare can be felt in particular and the role of fisherwomen who support family welfare in general. The method used is by sharing knowledge and experience with the theme "The Role of Fisherwomen in Improving Family Welfare in Sindanglaut, Carita Beach Tourism Area, Pandeglang" which is delivered by lectures and also direct interviews to fishermen (men and women) communicatively. As for the results of this community service program, it can improve Human Resources (HR), especially for fisherwomen, in addition to the spirit of improving family welfare that they have done, they also continue to strive to improve economic welfare through processing, and increasing sales of processed products and fresh fish. It is hoped that it can reduce poverty levels among fishermen, especially in Durung Village Rt008/02 SindangLaut Village, Carita District, Pandeglang Regency, Tangerang.